The Story Within Us : Women Prisoners Reflect on Reading - Sweeney, Megan, 1967- (University of Illinois Press, 2012)
This book features in-depth oral interviews with eleven incarcerated women, each of whom offers a narrative of her life and her reading experiences within prison walls. The women share powerful stories about their complex and diverse efforts to negotiate difficult relationships, exercise agency in restrictive circumstances, and find meaning and beauty in the midst of pain. Their shared emphases on abuse, poverty, addiction, and mental illness illuminate the pathways that lead many women to prison and suggest possibilities for addressing the profound social problems that fuel crime. Framing the narratives within an analytic introduction and reflective afterword, the editor highlights the crucial intellectual work that the incarcerated women perform despite myriad restrictions on reading and education in U.S. prisons. These women use the limited reading materials available to them as sources of guidance and support and as tools for self-reflection and self-education. Through their creative engagements with books, the women learn to reframe their own life stories, situate their experiences in relation to broader social patterns, deepen their understanding of others, experiment with new ways of being, and maintain a sense of connection with their fellow citizens on both sides of the prison fence.